Pengurangan Kadar Chrom dari Limbah Cair Industri Menggunakan Sistem Sub-Surface Flow Constructed Wetland (Ssf-Cw) dengan Tanaman Akar Wangi pada Media Kerikil dan Granul Fly Ash - Hasanah, Nur Hayati; Yuliansyah, Ahmad Tawfiequrrahman; Prasetya, Agus (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Sub-Surface Flow Constructed Wetland (SSF-CW) is one of the engineered of sewage treatment systems built and designed involving aquatic plants, soil or other media and related microbes, with more controlled treatment using sub-surface flow types. The purpose of this study was to determine the ability of aquatic plants to reduce of chromium (Cr) in wastewater, to understand the effect of fly media ash and gravel media in the constructed wetland system in reducing chrom  in wastewater. The Constructed Wetland was designed made of plastic with the Sub-Surface Flow Constructed Wetland (SSF-CW) model with 3 zones, zone 1 which is inlet zone and zone 3 which is outlet having dimensions of 37 x 54.5 x 60 cm, while zone 2 which is a reaction zone with dimensions 75 x 52.6 x 43.5 cm. The results showed that overall chrom removal from wastewater in RI, RII, RIII was 85.76, 93.24, and 74.69%, respectively. During the study, there was a growth of the plants, indicated by the presence of new shoots and an increase in the weight of plants. The kinetic model for reducing chromium content in wastewater at the RI, RII and RIII reactors follows the first order equation with a value of k value of 5.3411; 2,4006; and 0.1330.